Course Internationalization Through Virtual Exchange: Students' Reflections About "Seeing the World Through the Lens That is Soccer". (December 2021) - Coche, Roxane
Virtual exchange (VE) is an emergent but promising trend in course internationalization, which consists of using technology to interact and work with another class located in another city/country to develop digital skills and intercultural competence. After a VE project was implemented in a sports-related communication course, students reflected on their experience in a short paper or a video. This case study is a qualitative analysis of these 17 reflections. Despite some complications, students indicated they learned much about cultural differences and would be keen to repeat the VE experience.